Teacher Professional Practical Training Module for Teachers Assistant in Guiding Practice Students in Managing Learning - Sangadji, Kapraja; Sangadji, Bokimains; Kisno (Journal of Education Technology, 2022)
The ability to accompany teachers in guiding student practitioners that is less than optimal causes a decrease in the quality of learning management. Lack of understanding and awareness of managing learning in terms of learning practices must receive serious attention, provide instruments in clear modules or guidelines, and post-implementation evaluations. This study aims to develop a teacher's professional practice training module for teacher assistants to guide students' practice in managing to learn. The type of model and design used is research and development by combining the Rowntree, Borg, and Gall models. The study subjects were assistant teachers at the Early Childhood Education Unit and Elementary School, totaling 40 people. Methods of collecting data through observation, interviews, and documentation studies. The data analysis techniques are descriptive qualitative analysis and statistical inferential. The results of the study were the results of the assessment by material experts (93.64%), design experts (88.57%), and media experts (86.75%), who stated that the teacher training professional practice module developed was feasible to use. The results of individual and group trials of 30 respondents also experienced an increase, with a free test score of 76.33% and a post-test score of 84.37%. These results indicate an increase in the ability to guide teachers accompanying students with learning outcomes of 8.04, so the teaching professional practice training module for accompanying teachers is feasible and effective.